Clinically significant depressive symptoms and sexual behaviour among men who have sex with men. Issue 3 (May 2017) - Miltz, Ada R.; Rodger, Alison J.; Sewell, Janey; Speakman, Andrew; Phillips, Andrew N.; Sherr, Lorraine; Gilson, Richard J.; Asboe, David; Nwokolo, Nneka C.; Clarke, Amanda; Gompels, Mark M.; Allan, Sris; et al.
Abstract : Background: The relationship between depression and sexual behaviour among men who have sex with men (MSM) is poorly understood. Aims: To investigate prevalence and correlates of depressive symptoms (Patient Health Questionnaire-9 score ≥10) and the relationship between depressive symptoms and sexual behaviour among MSM reporting recent sex. Method: The Attitudes to and Understanding of Risk of Acquisition of HIV (AURAH) is a cross-sectional study of UK genitourinary medicine clinic attendees without diagnosed HIV (2013–2014). Results: Among 1340 MSM, depressive symptoms (12.4%) were strongly associated with socioeconomic disadvantage and lower supportive network. Adjusted for key sociodemographic factors, depressive symptoms were associated with measures of condomless sex partners in the past 3 months (≥2 (prevalence ratio (PR) 1.42, 95% CI 1.17–1.74; P =0.001), unknown or HIV-positive status (PR 1.43, 95% CI 1.20–1.71; P <0.001)), sexually transmitted infection (STI) diagnosis (PR 1.46, 95% CI 1.19–1.79; P <0.001) and post-exposure prophylaxis use in the past year (PR 1.83, 95% CI 1.33–2.50; P <0.001). Conclusions: Management of mental health may play a role in HIV and STI prevention.